"Yes, I can": what is the role of perceived self-efficacy in violent online-radicalisation processes of "homegrown" terrorists?. Issue 3 (1st September 2020) - Schlegel, Linda
ABSTRACT: Radicalisation is influenced by a multitude of factors such as situational, social and psychological factors, including social-cognitive processes. This article explores how homegrown extremists are influenced by their perceived agency and how the beliefs of their own abilities to change their situation are directly shaped by the online-propaganda they consume using ISIS propaganda as a case study. The article serves as an exploratory analysis of the potential explanatory qualities of Bandura's theory of self-efficacy. This preliminary theoretical work explores how online-propaganda seeks to increase perceived personal self-efficacy to inspire action. The findings indicate that an increased focus on agency beliefs may facilitate a more holistic understanding of the psycho-social processes influencing radicalization and factors driving certain individuals to perpetrate violence while others do not. More research needs to be conducted, but this work is a first exploratory step in advancing our understanding of self-efficacy beliefs in the radicalization of homegrown extremists.